The effects of teaching a book unit that contains controversial scholars’ opinions on the critical thinking of high school students - Aljohani, Majdi Ahmed Hammad; Alqarni, Mohammed Saad (Journal of Curriculum and Teaching Methodology, 2024)
The study aimed to investigate the impact of teaching a unit containing controversial issues in the Islamic jurisprudence curriculum on the critical thinking skills of secondary school students. To achieve this goal, the researcher used a quasi-experimental design based on dividing students into two groups (experimental and control) with pretest and posttest measurements. The researcher prepared the study instruments, including the Watson-Glaser Critical Thinking Appraisal, in addition to designing a unit containing controversial issues. The study sample consisted of thirty-eight students in the third year of secondary school in Yanbu Governorate. The results indicated that the instructional unit significantly contributed to improving and developing the level of critical thinking among students. Additionally, there were statistically significant differences in the average scores of students between the control and experimental groups in favor of the experimental group in critical thinking. Based on these findings, the study made several recommendations, including the need to develop curricula and integrate critical thinking skills into all subjects, as well as the importance for curriculum developers to focus on concepts of jurisprudential controversy, utilize them, and increase their inclusion in the Islamic jurisprudence curriculum.